Development and analysis of simulation of liquid-propellant rocket engine pump head curve obtaining process - D. A. Savchin; V. P. Nazarov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper describes the model of the centrifugal pump head curve obtaining process which helps in consideration of the implementation of automated systems in liquid-propellant rocket engine manufacturing. The work contains the simulation of automated and non-automated head curve obtaining. The developed model shows that the automated process exceeds the non-automated analog in terms of error values and labor intensity